Kerangka Aktivitas Research Based Learning Dengan Pendekatan Steam: "Analisis Teknologi Irigasi Kapilaritas Dan Tetes Serta Penyiram Otomatis Berbasis Panel Surya Dengan Smart Sensor Untuk Meningkatkan Literasi Perubahan Iklim Siswa” - Okti Anis Safiati; Dafik; Puji Lestari; Syaiful Rahman (KRAKATAU (Indonesian of Multidisciplinary Journals), 2024)
Climate change literacy Refers to a deep understanding and awareness of climate change issues, including knowledge of the causes, impacts, and adaptation and mitigation strategies that can be implemented. These skills include not only theoretical knowledge but also practical skills to assess climate-related information, make decisions based on evidence, and participate in dialogue and action aimed at addressing climate challenges. With adequate literacy, individuals and communities can be more effective in identifying sustainable solutions, advocating for science-based policies, and contributing to global and local efforts to address climate change, thereby helping maintain ecological balance and maintaining quality of life for future generations. The aim of this research is to increase climate change literacy among students through the application of analysis and innovative irrigation technology, including capillarity irrigation, drip irrigation, and automatic irrigation systems powered by solar panels with smart sensor integration. The main output of this research is the development of a Research Based Learning (RBL) Activity Framework with a STEAM (Science, Technology, Engineering, Art and Mathematics) Approach which focuses on capillarity and drip irrigation technology, as well as automatic watering powered by solar panels with smart sensor integration. This framework is designed to provide systematic and structured guidance for educators and students in exploring scientific concepts and their application in irrigation technology. The method used in this research is descriptive narrative related to the student activity framework. The results of this research are the results of planting a drip and absorption system and the use of solar panels in an automatic sprinkler system to increase students' climate change literacy. In this research, a Research Based Learning model was applied which was integrated with the STEAM (Science, Technology, Engineering, Art, and Mathematics) approach to increase students' climate change literacy by presenting STEAM problem solving in learning. The STEAM problem raised in this research is the impact of climate change on the environment. The results of this research are in the form of a STEAM problem formulation, integration of RBL_STEAM syntax and including a description of five STEAM studies, and finally the development of a climate change literacy assessment instrument.